A method for preparing tantalum-niobium tailings concrete
Through tailings drainage, water-adhesive ratio adjustment, application of pozzolanic ash materials and dosage control methods, the problems of low utilization rate of tantalum niobium tailings and poor concrete performance are solved, and efficient utilization of tailings is achieved and the strength and economic benefits of concrete are improved.
Patent Information
- Application Number
- CN202411588786.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-04-04
AI Technical Summary
The existing tantalum niobium tailings have low utilization and poor performance of prepared concrete. The main problems include high moisture content, high water absorption, poor workingability and unstable strength.
High-efficiency tantalum niobium tailings concrete is prepared by tailings drainage, water-adhesive ratio adjustment, application of pozzolanic material and control of the doping amount of ultrafine powder and fine powder. Specific steps include draining tailings, adjusting the water-gluing ratio with water-reducing enhancers, adding pozzolanic materials to improve water tightness, and controlling the tailings mixing below 40% of the total aggregate.
It greatly improves the utilization rate of tantalum niobium tailings and the economic benefits of concrete, ensures that the final strength of concrete meets the design strength requirements, improves product performance and quality, and reduces production costs.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of construction materials, and in particular relates to a method for preparing tantalum-niobium tailings concrete. Background Art
[0002] Tantalum-niobium ore is produced in albite-feldspar granite. The tailings are mainly feldspar, with clay and mica minerals accounting for about 5-7%, and sodium oxide and potassium oxide accounting for 6-8%. In the past, the resource utilization of tailings was mainly used in the ceramic industry. In recent years, the sluggish domestic ceramic market has led to a significant decline in the utilization rate of tantalum-niobium tailings. In order to reduce the impact of market conditions on tailings disposal, it is necessary to expand the resource utilization of tantalum-niobium tailings. Using tantalum-niobium tailings to make building materials is an effective way to dispose of tantalum-niobium tailings in large quantities.
[0003] Tantalum-niobium tailings can be divided into three particle size grades: ultrafine powder, fine powder and coarse powder. About 90% of the ultrafine powder particles are smaller than 0.075 mm, and about 70% of the fine powder particles are smaller than 0.075 mm. The coarser particles of the two are mostly mica flakes. Nearly 90% of the coarse powder particles are larger than 0.1 mm, and the fineness modulus is about 0.9. The particle size distribution is as follows: Figures 1 to 3 Its element composition table is shown in Figure 4 As shown. The clay content of ultrafine powder is high, and it forms hard lumps after squeezing and dehydration. It must be crushed and sieved before use. The particles of fine powder and coarse powder are slightly coarse and basically loose. Due to the high water absorption rate of tantalum-niobium tailings, the water absorption rate of ultrafine powder tantalum-niobium tailings exceeds 20%, the water absorption rate of fine powder is greater than 17%, and the water absorption rate of coarse powder is also around 10%. The workability of high-mixed tantalum-niobium tailings concrete is poor, and it is easy to bleed water during vibration, which is not conducive to the development of concrete strength. In addition, because of the fine particles, high content of clay and flaky minerals, the fluidity of concrete mixture is not good, so it can only be used in small amounts. In particular, the physical and chemical properties of ultrafine powder tailings are not conducive to the application as building materials, and there has been no effective way to dispose of them. The mixing ratio of tantalum-niobium tailings in concrete is the key to whether the application of tantalum-niobium tailings in green building materials is economically beneficial.
[0004] At present, there are several main problems in preparing concrete from tantalum-niobium tailings: (1) Tantalum-niobium tailings have high water content and are difficult to dry, which affects the control of water-binder ratio during production and directly causes unstable product quality; (2) Tantalum-niobium tailings have fine particles and high water demand, which is not conducive to the workability and strength development of concrete; (3) According to the analysis results of the mineral composition of the original ore and the composition of the tailings, the clay mineral content in the ultrafine powder may be high, which will increase the water consumption of concrete and reduce the bonding force between aggregate and cement paste; the mineral structure of flaky mica has low mechanical strength, which has an adverse effect on the fluidity of fresh concrete and also hinders the formation of a normal cementing structure of concrete, causing expansion and damage after absorbing water, reducing the strength of concrete and other negative effects. The above factors may also affect the durability of concrete. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of low utilization rate of existing tantalum-niobium tailings and poor performance of the prepared concrete, and to provide a method for preparing tantalum-niobium tailings concrete, which can greatly improve the utilization rate of tailings and the economic benefits of products, while effectively ensuring that the final strength of concrete meets the design strength requirements, thereby improving product performance and quality.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing tantalum-niobium tailings concrete, the specific steps are as follows, including: (1) Tailings drainage: The tailings only need to be drained of the free water contained therein. Before stirring, the tailings are still wet, and the water content of the tailings must be measured before stirring to control the water consumption; (2) Adjustment of water-binder ratio: Use an appropriate amount of water-reducing enhancer to reduce the water-binder ratio, improve concrete strength, and reduce tailings water absorption and vibration water seepage; (3) Application of volcanic ash materials: Adding volcanic ash active materials will react with cement hydration product Ca(OH)2 to generate hydrated calcium silicate gel, which fills micropores, increases the water tightness of concrete, isolates the channels for water in and out, prevents clay minerals and mica from contacting water, and maintains the stability of concrete volume; (4) The amount of ultrafine powder and fine powder added should be controlled below 40% of the total aggregate to reduce the viscosity and water absorption of concrete, so as to obtain better workability and stable concrete strength.
[0007] Furthermore, the tantalum-niobium tailings concrete includes three grades according to the prepared concrete strength, namely, controlled low-strength material CLSM, C20 and C30. Among the required preparation materials, tailings are the main solid waste filler, the curing binder includes ordinary Portland cement and water-reducing enhancer, and the volcanic ash active materials are slag powder, silica fume and fly ash. Different material combinations can be used to achieve the strength of the bonding and curing and product quality requirements.
[0008] Furthermore, the weight ratio range of each material of the tantalum-niobium tailings CLSM concrete is as follows: ultrafine powder tailings 0-25%, fine powder tailings 0-30%, coarse powder tailings 30-50%, fly ash 3-10%, slag powder 3-5%, 42.5 ordinary Portland cement 3-5%, and water reducing enhancer 0.3-0.5%.
[0009] Furthermore, the weight ratio range of each material of the tantalum-niobium tailings C20 concrete is as follows: ultrafine powder tailings 0~25%, fine powder tailings 0~30%, coarse powder tailings 30~45%, fly ash 0~15%, slag powder 5~10%, 42.5 ordinary Portland cement 8~15%, and water reducing enhancer 0.2~0.5%.
[0010] Furthermore, the weight ratio range of each material of the tantalum-niobium tailings C30 concrete is as follows: ultrafine powder tailings 0~20%, fine powder tailings 0~25%, coarse powder tailings 20~50%, fly ash 0~10%, slag powder 5~15%, 42.5 ordinary Portland cement 10~15%, and water reducing enhancer 0.3~0.6%.
[0011] Furthermore, in the preparation of the tantalum-niobium tailings CLSM concrete, the water-binder ratio is preferably 0.4.
[0012] Furthermore, in the preparation of the tantalum-niobium tailings C20 concrete, the water-binder ratio is preferably 0.32.
[0013] Furthermore, in the preparation of the tantalum-niobium tailings C30 concrete, the water-binder ratio is preferably 0.30.
[0014] Compared with the prior art, the advantages of the technical solution of the present invention are: (1) The present invention adopts the whole tailings mix ratio, and the strength of the concrete produced includes three grades of controlled low strength material CLSM, C20 and C30, and the tailings mixing ratio reaches 60% to 90%, which greatly improves the utilization rate of tailings and the economic benefits of products; (2) The tailings of the present invention are still in a wet state before mixing, which not only saves energy consumption for drying, but also makes it easier for the mixture to obtain good workability. Too dry tailings absorb a large amount of water during the mixing process, which will make the mixture unable to obtain sufficient fluidity and cause the concrete to collapse too much in a short time, which is not conducive to operation; (3) The weight ratio of each material in the concrete of the present invention can be determined according to the properties of the raw materials, the product strength requirements, and the local raw material supply conditions. The amount of water added depends on the water content, water absorption rate and water-binder ratio of the tailings. Different material combinations can achieve the strength and product quality requirements of cementation and curing. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1It is a schematic diagram of particle size distribution of ultrafine powder of tantalum-niobium tailings in the prior art; Figure 2 It is a schematic diagram of particle size distribution of tantalum-niobium tailings fine powder in the prior art; Figure 3 It is a schematic diagram of particle size distribution of coarse powder of tantalum-niobium tailings in the prior art; Figure 4 This is an element analysis table of tantalum-niobium tailings in the prior art; Figure 5 This is a table showing the compressive strength test results of tantalum-niobium tailings concrete in Examples 1 to 6 of the present invention. DETAILED DESCRIPTION Example 1
[0016] To make the present invention more clear, the preparation method of tantalum-niobium tailings concrete of the present invention is further described below in conjunction with the accompanying drawings. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0017] In this embodiment, the preparation of CLSM of tantalum-niobium tailings is taken as an example: Take the components according to the following weight: ultrafine powder tantalum niobium tailings (dry) 50, coarse powder tantalum niobium tailings (dry) 50, slag powder 7, 42.5 ordinary Portland cement 7, water reducing enhancer 0.45, water-cement ratio 0.4.
[0018] The ultrafine powder agglomerates are crushed to a particle size of less than 0.5 mm; the tailings are mixed and pre-wetted, the cementitious material is added with water and a water-reducing enhancer to form a slurry in a mixer, and then the pre-wetted tailings powder is added and stirred evenly, and cured in a curing room for 28 days to obtain the slurry. Example 2
[0019] In this embodiment, the preparation of CLSM of tantalum-niobium tailings is taken as an example: Take the components according to the following weight: ultrafine powder tantalum niobium tailings (dry) 24, fine powder tantalum niobium tailings (dry) 29, coarse powder tantalum niobium tailings 66, fly ash 14, slag powder 8, 42.5 ordinary Portland cement 8, water reducing enhancer 0.4, water-cement ratio 0.4.
[0020] The ultrafine powder agglomerates are crushed to a particle size of less than 0.5 mm; the tailings are mixed and pre-wetted, the cementitious material is mixed with water and a water-reducing enhancer in a mixer to form a slurry, and then the pre-wetted tailings powder is added and mixed evenly, and cured in a curing room for 28 days to obtain the product. This embodiment is also used for roadbed construction materials of a 50-meter demonstration road. Example 3
[0021] In this embodiment, the preparation of C20 concrete from tantalum-niobium tailings is taken as an example: Take the components according to the following weight: ultrafine powder tantalum niobium tailings (dry) 30, coarse powder tantalum niobium tailings 45, slag powder 12, 42.5 ordinary Portland cement 15, water reducing enhancer 0.5, water-cement ratio 0.32.
[0022] The ultrafine powder agglomerates are crushed to a particle size of less than 0.5 mm; the tailings are mixed and pre-wetted, the cementitious material is added with water and a water-reducing enhancer to form a slurry in a mixer, and the pre-wetted tailings powder is added and mixed evenly, and cured in a curing room for 28 days to obtain the slurry. Example 4
[0023] In this embodiment, the preparation of C20 concrete from tantalum-niobium tailings is taken as an example: Take the components according to the following weight: ultrafine powder tantalum niobium tailings (dry) 32, coarse powder tantalum niobium tailings 51, slag powder 11, 42.5 ordinary Portland cement 12, water reducing enhancer 0.4, water-cement ratio 0.32.
[0024] The ultrafine powder agglomerates are crushed to a particle size of less than 0.5 mm; the tailings are mixed and pre-wetted, the cementitious material is added with water and a water-reducing enhancer to form a slurry in a mixer, and the pre-wetted tailings powder is added and mixed evenly, and cured in a curing room for 28 days to obtain the slurry. Example 5
[0025] In this embodiment, the preparation of tantalum-niobium tailings C30 concrete is taken as an example: Take the components according to the following weight: ultrafine powder tantalum niobium tailings (dry) 6, fine powder tantalum niobium tailings 67, slag powder 16, 42.5 ordinary Portland cement 20, water reducing enhancer 0.47, water-cement ratio 0.3.
[0026] The ultrafine powder agglomerates are crushed to a particle size of less than 0.5 mm; the tailings are mixed and pre-wetted, the cementitious material is added with water and a water-reducing enhancer to form a slurry in a mixer, and the pre-wetted tailings powder is added and mixed evenly, and cured in a curing room for 28 days to obtain the slurry. Example 6
[0027] In this embodiment, the preparation of tantalum-niobium tailings C30 concrete is taken as an example: Take the components according to the following weight: 43% fine powder tantalum-niobium tailings, 75% coarse powder tantalum-niobium tailings, 30% slag powder, 42.5% ordinary Portland cement, 30% silica fume, 2.5% water-reducing enhancer, and 0.3% water-cement ratio.
[0028] The tailings are mixed and pre-wetted, the cementitious material is mixed with water and a water reducing agent in a mixer to form a slurry, and then the pre-wetted tailings powder is added and mixed evenly, and cured in a curing room for 28 days to obtain the obtained material. This embodiment is also used for the surface construction material of a 50-meter demonstration road.
[0029] The tantalum-niobium ore tailings concrete prepared in the above Examples 1 to 6 are numbered as test samples 1 to 6, respectively, and the compression test results thereof are as follows: Figure 5 shown.
[0030] Due to the high water absorption rate of tailings, the present invention has a significant negative impact on the strength development of concrete. In order to achieve the design strength and reduce production costs, a large amount of volcanic ash materials such as fly ash, slag powder and silica fume are used. These volcanic ash materials are also industrial by-products and have environmental protection significance for energy saving and carbon reduction. Due to the high proportion of volcanic ash materials, the initial strength development is relatively slow, and its 56-day strength is usually tested. Figure 5 The test results show that the 28-day compressive strength of each embodiment is close to or meets the strength of the design grade, and the 56-day strength all meets the design strength. It can be seen from the strength development of each embodiment in the table that compared with the almost stagnant strength development of traditional cement-based concrete after 28 days, the strength development of the tailings concrete of the present invention is still strong during the period from 28 days to 56 days. The laboratory test results show that the strength development lasts for more than 6 months or even 1 year. It is judged that the tailings concrete of the present invention has better durability.
[0031] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.
Claims
1. A method for preparing tantalum-niobium tailings concrete, comprising the following specific steps, characterized in that: (1) Tailings drainage: The tailings only need to be drained of the free water contained therein. Before stirring, the tailings are still wet, and the water content of the tailings must be measured before stirring to control the water consumption; (2) Adjustment of water-binder ratio: Use an appropriate amount of water-reducing enhancer to reduce the water-binder ratio, improve concrete strength, and reduce tailings water absorption and vibration seepage; (3) Application of volcanic ash materials: Adding volcanic ash active materials will react with cement hydration product Ca(OH)2 to generate hydrated calcium silicate gel, which fills micropores, increases the water tightness of concrete, isolates the channels for water in and out, prevents clay minerals and mica from contacting water, and maintains the stability of concrete volume; (4) The amount of ultrafine powder and fine powder added should be controlled below 40% of the total aggregate amount to reduce the viscosity and water absorption of concrete and obtain better workability and stable concrete strength.
2. The method for preparing tantalum-niobium tailings concrete according to claim 1, characterized in that: The tantalum-niobium tailings concrete includes three grades according to the prepared concrete strength, namely controlled low-strength material CLSM, C20 and C30. Among the required preparation materials, tailings are the main solid waste filler, the curing binder includes ordinary Portland cement and water-reducing enhancer, and the volcanic ash active materials are slag powder, silica fume and fly ash.
3. The method for preparing tantalum-niobium tailings concrete according to claim 2, characterized in that: The weight proportion ranges of various materials of the tantalum-niobium tailings CLSM concrete are as follows: ultrafine powder tailings 0-25%, fine powder tailings 0-30%, coarse powder tailings 30-50%, fly ash 3-10%, slag powder 3-5%, 42.5 ordinary Portland cement 3-5%, and water reducing enhancer 0.3-0.5%.
4. The method for preparing tantalum-niobium tailings concrete according to claim 2, characterized in that: The weight ratio ranges of the various materials of the tantalum-niobium tailings C20 concrete are as follows: ultrafine powder tailings 0~25%, fine powder tailings 0~30%, coarse powder tailings 30~45%, fly ash 0~15%, slag powder 5~10%, 42.5 ordinary Portland cement 8~15%, and water reducing enhancer 0.2~0.5%.
5. The method for preparing tantalum-niobium tailings concrete according to claim 2, characterized in that: The weight ratio ranges of the various materials of the tantalum-niobium tailings C30 concrete are as follows: ultrafine powder tailings 0~20%, fine powder tailings 0~25%, coarse powder tailings 20~50%, fly ash 0~10%, slag powder 5~15%, 42.5 ordinary Portland cement 10~15%, and water reducing enhancer 0.3~0.6%.
6. The method for preparing tantalum-niobium tailings concrete according to any one of claims 2 to 5, characterized in that: In the preparation of the tantalum-niobium tailings CLSM concrete, the water-binder ratio is preferably 0.
4.
7. The method for preparing tantalum-niobium tailings concrete according to any one of claims 2 to 5, characterized in that: In the preparation of the tantalum-niobium tailings C20 concrete, the water-binder ratio is preferably 0.
32.
8. The method for preparing tantalum-niobium tailings concrete according to any one of claims 2 to 5, characterized in that: In the preparation of the tantalum-niobium tailings C30 concrete, the water-binder ratio is preferably 0.30.